প্রজুক্তির স্পন্দন A Walkway of Knowledge AGARGAON, DHAKA - Khan, Tabriz Rashid (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2017.